2018
DOI: 10.2478/fhort-2018-0004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arbuscular mycorrhizal fungi on early development of persimmon seedlings

Abstract: The present study evaluated the effects of five species of arbuscular mycorrhizal fungi (AMF) on vegetative development parameters and nutrient uptake of persimmon (Diospyros kaki L.) seedlings. The experiment was carried out in a completely randomized experimental design with six treatments involving AMF inoculation (non-inoculated; Dentiscutata heterogama, Claroideoglomus etunicatum, Rhizophagus clarus, Acaulospora scrobiculata and A. morrowiae), in sterile soil (Oxisol -Dystrophic Red Latosol) under greenho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 33 publications
0
16
0
3
Order By: Relevance
“…Arbuscular mycorrhizal fungi (AMF), for their ability to exploit larger substrate volumes and favor the absorption of nutrients, can increase the productivity of nurseries and reduce the production time of seedlings, thus improving their nutritional status and accelerating their growth (Santos et al 2011, Machineski et al 2018. In addition, AMF may play a key role in the mineralization process of organic matter (Paterson et al 2016), increasing the soil fertility (Johnson et al 2016), and may also be stimulated by the addition of organic matter to the soil (Sheldrake et al 2017).…”
Section: Palavras-chavementioning
confidence: 99%
See 1 more Smart Citation
“…Arbuscular mycorrhizal fungi (AMF), for their ability to exploit larger substrate volumes and favor the absorption of nutrients, can increase the productivity of nurseries and reduce the production time of seedlings, thus improving their nutritional status and accelerating their growth (Santos et al 2011, Machineski et al 2018. In addition, AMF may play a key role in the mineralization process of organic matter (Paterson et al 2016), increasing the soil fertility (Johnson et al 2016), and may also be stimulated by the addition of organic matter to the soil (Sheldrake et al 2017).…”
Section: Palavras-chavementioning
confidence: 99%
“…12 to the treatment without inoculation (Machineski et al 2018). This result is related to the performance of the extraradicular hyphae, that promote a greater root area exploration and increases the absorption of nutrients with low mobility in the soil (El-Shaik & Mohammed 2009).…”
Section: Amf Isolatesmentioning
confidence: 99%
“…In the absence of phosphate fertilization, the inoculation of seedlings of carambola (star fruit) with Rhizoglomus clarum promoted the highest increments in the production of dry matter, height and contents of nitrogen, calcium and potassium (VITORAZI FILHO et al, 2017). Machineski et al (2018) observed that inoculation with AMF improved the initial development of persimmon seedlings. While Boyer et al (2016), affirmed that the greater the ability to specify the genotypes of strawberries colonized by AMF, the higher will be the understanding of its beneficial effects, mainly on resistance or tolerance to pathogens.…”
Section: Introductionmentioning
confidence: 95%
“…Soil microorganisms present potential for interaction with agricultural crops and promote their development (MACHINESKI et al, 2018). Arbuscular mycorrhizal fungi (AMF) (phylum: Glomeromycota) are cited among these benefical organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Se sabe que esta relación simbiótica promueve el crecimiento de las plantas hospederas y que las raíces de estas pueden convivir con más de una especie de HMA. La micorrización también incrementa la calidad de plantas en vivero y mejora el crecimiento después del trasplante de invernadero a campo (Ortas y Ustuner, 2014;Machineski et al, 2018). Por otro lado, no existe una especif icidad hongo planta, pero si production were reached in the substrate.…”
Section: Introductionunclassified